The potential of using itaconate as treatment for inflammation-related heart diseases - Hui-Chen Ku; Ta-Chung Shen; Ching-Feng Cheng (Tzu Chi Medical Journal)
Intracellular metabolites can cause critical changes in biological functions. Itaconate is perhaps the most fascinating substance in macrophages. Lipopolysaccharide can activate aconitate decarboxylase 1 and induces the generation of itaconate from the tricarboxylic acid cycle by decarboxylation of cis-aconitate. It has been reported that itaconate has beneficial effects on inflammation and oxidation. The mechanisms involved in these effects include the suppression of succinate dehydrogenase, the activation of nuclear factor E2-related factor 2 by alkylation of Kelch-like ECH-associated protein 1, suppression of aerobic glycolysis through regulation of glyceraldehyde-3-phosphate dehydrogenase and fructose-bisphosphate aldolase A, and suppression of IκBζ translation through activating transcription factor 3 activation. All of these findings elucidated the possible therapeutic implications of itaconate in inflammation-related diseases. In this review, we highlight that itaconate is a crucial molecule of the immunomodulatory response in macrophages and can regulate between immune response and cardiovascular metabolism. Furthermore, these discoveries suggest that itaconate is a very novel therapeutic molecule for the treatment of inflammation-related heart diseases.